Mapping the (mis)match of university degrees in the graduate labor market - Manuel Salas-Velasco (Journal for Labour Market Research, 2021)
This paper contributes to the scarce literature on the topic of horizontal education-job mismatch in the labor market for graduates of universities. Field-of-study mismatch or horizontal mismatch occurs when university graduates, trained in a particular field, work in another field at their formal qualification level. The data used in the analysis come from the first nationally representative survey of labor insertion of recent university graduates in Spain. By estimating a multinomial logistic regression, we are able to identify the match status 4~years after graduation based on self-assessments. We find a higher likelihood of horizontal mismatch among graduates of Chemistry, Mathematics, Physics, Pharmacy, and Languages and Literature. Only graduates in Medicine increase the probability of being adequately matched in their jobs. It may be hypothesized that horizontal mismatch is more likely among those graduates in degree fields that provide more general skills and less likely among those from degree fields providing more occupation-specific skills. Other degrees such as Business Studies, and Management and Economics Studies increase the probability of being vertically mismatched (over-educated). Vertical mismatch preserves at least some of the specific human capital gained through formal educational qualifications. However, some workers with degrees in Labor Relations and Social Work are in non-graduate positions and study areas unrelated to their studies. The paper also shows that graduates in the fields of health sciences and engineering/architecture increase the probability of achieving an education-job match after external job mobility.
Keywords: J24; J63; I21; C50; 330; Education-job mismatch; Higher education; Horizontal mismatch; Job turnover; Multinomial logistic regression; Spanish university degrees